ANALISIS KUALITAS PELAYANAN PUBLIK PADA KANTOR KELURAHAN KUALA JELAI KECAMATAN JELAI KABUPATEN SUKAMARA: ANALYSIS OF THE QUALITY OF PUBLIC SERVICESOFFICE KELURAHAN KUALA JELAI, KECAMATAN JELAI, SUKAMARA DISTRICT - Mu'ti, Abdul; Bernardianto, Raden Biroum; Sion, Holten (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Kuala Jelai Urban Village, Jelai District, Sukamara Regency has a function of providing public services in accordance with existing SOPs to ensure optimal quality service. This study of the service quality of the kelurahan office aims to analyze the service quality of the Kuala Jelai Kelurahan Office. This research was conducted with a qualitative descriptive approach, with interview data collection methods and field observations. Research informants consisted of personnel from the Kuala Jelai Kelurahan Office as service providers and several communities as service recipients determined by purposive sampling. Research studies that are based on 5 (five) dimensions of service, namely: 1). Tangible variable dimensions. 2). Dimensions of the Reliability variable. 3). Responsiviness variable dimensions. 4). Assurance variable dimensions. 5). The Emphaty variable dimension shows 4 (four) variables included in the